2022
DOI: 10.31234/osf.io/akz5v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing the automaticity features of the Affect Misattribution Procedure: The roles of awareness and intentionality

Abstract: The Affect Misattribution Procedure (AMP) is a measure of implicit evaluations, designed to index the automatic (unintentional) retrieval of evaluative knowledge. The AMP effect consists in participants evaluating neutral target stimuli more positively when preceded by positive primes and more negatively when preceded by negative primes. Hughes et al. (2022) questioned the automaticity of the AMP based on an awareness effect, i.e., the finding that AMP effects were larger when participants indicated that their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 47 publications
(96 reference statements)
1
16
0
Order By: Relevance
“…In four experiments, Kurdi et al (2022) successfully replicated and extended Hughes et al's (2022, experiment 2) procedure and effect. However, they dismiss the results of these replications as "uninformative with respect to the underlying theoretical mechanism [i.e., awareness in the AMP effect]".…”
Section: Ian Hussey and Jamie Cumminssupporting
confidence: 57%
See 3 more Smart Citations
“…In four experiments, Kurdi et al (2022) successfully replicated and extended Hughes et al's (2022, experiment 2) procedure and effect. However, they dismiss the results of these replications as "uninformative with respect to the underlying theoretical mechanism [i.e., awareness in the AMP effect]".…”
Section: Ian Hussey and Jamie Cumminssupporting
confidence: 57%
“…We replicated and extended this effect in a larger second dataset, showing that the effect is replicable and that these problematic correlations are larger for the AMP than five other common implicit measures. Based on the line of reasoning of Kurdi et al (2022), we therefore found evidence against the AMP effect being unaware. Finally, the observed heterogeneity in tendency to demonstrate AMP effects implies the task is measurement non-invariant between participants.…”
Section: Ian Hussey and Jamie Cumminsmentioning
confidence: 85%
See 2 more Smart Citations
“…We do not share these concerns about the validity of the AMP. We believe that in its totality, available evidence overwhelmingly supports the construct validity of the AMP as a measure of implicit evaluations (for a review, see Payne & Lundberg, 2014), and the specific concerns raised by Bar-Anan and Nosek (2011) and Hughes et al (2022) have been laid to rest in followup work by Payne et al (2012) and Kurdi, Melnikoff, et al (2022). Moreover, we are generally of the view that susceptibility to relational information should not be used to judge the construct validity of measures of implicit evaluation.…”
Section: Additional Implications For Methods and Theorymentioning
confidence: 97%